Comparison between 2000 and 2018 on the reporting of statistical significance and clinical relevance in physiotherapy clinical trials in six major physiotherapy journals: a meta-research design. Issue 1 (3rd January 2022) - Verhagen, Arianne; Stubbs, Peter William; Mehta, Poonam; Kennedy, David; Nasser, Anthony M; Quel de Oliveira, Camila; Pate, Joshua W; Skinner, Ian W; McCambridge, Alana B
Abstract : Design: Meta-research. Objective: To compare the prevalence of reporting p values, effect estimates and clinical relevance in physiotherapy randomised controlled trials (RCTs) published in the years 2000 and 2018. Methods: We performed a meta-research study of physiotherapy RCTs obtained from six major physiotherapy peer-reviewed journals that were published in the years 2000 and 2018. We searched the databases Embase, Medline and PubMed in May 2019, and extracted data on the study characteristics and whether articles reported on statistical significance, effect estimates and confidence intervals for baseline, between-group, and within-group differences, and clinical relevance. Data were presented using descriptive statistics and inferences were made based on proportions. A 20% difference between 2000 and 2018 was regarded as a meaningful difference. Results: We found 140 RCTs: 39 were published in 2000 and 101 in 2018. Overall, there was a high prevalence (>90%) of reporting p values for the main (between-group) analysis, with no difference between years. Statistical significance testing was frequently used for evaluating baseline differences, increasing from 28% in 2000 to 61.4% in 2018. The prevalence of reporting effect estimates, CIs and the mention of clinical relevance increased from 2000 to 2018 by 26.6%, 34% and 32.8% respectively. Despite an increase in use in 2018, over 40% of RCTs failed to report effect estimates, CIs and clinical relevance of results. Conclusion: The prevalence of using p values remains high in physiotherapy research. Although the proportion of reporting effect estimates, CIs and clinical relevance is higher in 2018 compared to 2000, many publications still fail to report and interpret study findings in this way.